(untitled) (Marketing Journal, 2025)
To ensure the more rapid development of entrepreneurial activity, it is necessary to use modern and effective concepts of leadership in management. The article analyzes the theoretical foundations and concepts of leadership and, based on them, develops dir ections for the application of leadership in entrepreneurial activity. Suggestions and recommendations are given on the application of modern concepts of leadership.